Social-Ecological System constraints of Protected Areas. A case study of Mexican protected forests - Hakizimana Eugene; Arturo Lara Rivero; Ignacio Llamas Huitron (Fronteiras: Journal of Social, Technological and Environmental Science, 2019)
Protected Areas are worldwide accepted as conservation policy instrument. However, effectiveness of this instrument for sustainability management of protected resources is still problematic. It is in this context this paper investigates Social-Ecological System constraints which lead to unsuccessful situations in protected forests in Mexico. To achieve this objective, a methodology of E. Ostrom SES framework to carry out meta-analysis of case studies of Mexican forests is used. The results show that constraints are imbedded into attributes of governance of these resources by local communities through a set of variables whose patterns of interactions lead to successful or unsuccessful situations. These variables are variables characterizing governance system and variables characterizing actors’ system. The interactions of these variables lead to successful situations in case studies in which local community members highly participate in governance system.